2013
DOI: 10.1186/1744-9081-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of chronic neuropathic pain by environmental enrichment in mice well after the establishment of chronic pain

Abstract: BackgroundIn animal models, the impact of social and environmental manipulations on chronic pain have been investigated in short term studies where enrichment was implemented prior to or concurrently with the injury. The focus of this study was to evaluate the impact of environmental enrichment or impoverishment in mice three months after induction of chronic neuropathic pain.MethodsThirty-four CD-1 seven to eight week-old male mice were used. Mice underwent surgery on the left leg under isoflurane anesthesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 61 publications
2
79
0
7
Order By: Relevance
“…Similar to what is seen in patients, 61 some of these conditions subside once the pain is ameliorated. 62 We have shown that selective signs of neophobic anxiety (in the form of altered thigmotaxis in the zero maze but not open field assay) and memory impairment (novel object recognition and social memory but not novel location recognition) are present in our fracture/cast mice.…”
Section: Discussionmentioning
confidence: 70%
“…Similar to what is seen in patients, 61 some of these conditions subside once the pain is ameliorated. 62 We have shown that selective signs of neophobic anxiety (in the form of altered thigmotaxis in the zero maze but not open field assay) and memory impairment (novel object recognition and social memory but not novel location recognition) are present in our fracture/cast mice.…”
Section: Discussionmentioning
confidence: 70%
“…Paw withdrawal thresholds (g) to mechanical stimulation were measured in duplicate in each paw using an electronic von Frey anesthesiometer (IITC model Alemo 2390–5, Woodland Hills, CA) as described previously(31). Duration of hypersensitivity to cold stimulation was measured using the acetone method in the same animals used to assess mechanical hypersensitivity (32).…”
Section: Methodsmentioning
confidence: 99%
“…Environmental enrichment weakens both nerve injury-induced mechanical and cold hypersensitivity. It is also believed to lower the calcitonin gene-related peptide and concentration of substance P. On the other hand, an impoverished environment intensifies mechanical hypersensitivity [31] . Emerging targets like chemokines, Wnt pathway, and proteases have been shown to increase spinal cord neuroinflammation and chronic pain [32] .…”
Section: Pathophysiologymentioning
confidence: 99%